Kemampuan Berpikir Kritis Matematis melalui Model Education Coins of Mathematics Competition (E-COC) - Lestari, Yunia; Mujib, Mujib (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study was aimed to improve the ability of critical thinking mathematically through the application of Education Coins Of Mathematics Competition (E-COC) model in class X students. This research is Quasy Experimental Design research. The sampling technique was done by simple random class. Technique of collecting data by using test. Data analysis techniques used t-test. The prerequisite analysis test was performed by Liliefors method for normality test, Bartlett test for homogeneity test and N-Gain. Based on normality test results by using Liliefors test, homogeneity test with Bartlett and N-Gain test, it was found that the test result data from both groups were normal homogeneous and there was an increase in N-Gain. So for testing the hypothesis can be used t-test. Result of research and data analysis obtained t_hitung= 2,704 at N-Gian, while t_tabel=1,999. Therefore t_hitung>t_tabel then H rejected H1 accepted, meaning there was difference of improvement of critical thinking ability of mathematical student’s using model of Education Coins Of Mathematics Education (E-COC) and conventional learning model. Based on the research, it can be concluded the application of Education Coins Of Mathematics Education (E-COC) model can be improved the critical thinking ability of student’s.